Carbamazepine Induced Stevens - Johnson Syndrome: A Case Report - G, Manjunath; N, Sheetal; S, Pooja; P, Neelkantreddy; Y, Snehasri (Indian Journal of Pharmacy Practice)
Stevens-Johnson syndrome is mucocutaneous cell mediated hypersensitivity reaction which affects 2 to 3 cases per million. SJS is generally rare, but potentially life threatening and commonly drug induced. We report a case of 12-year-old male child admitted to paediatric intensive care unit at a tertiary care hospital with chief complaints of fever, abdomen pain, vomiting erythematous lesions and macular rashes all over the body including face, neck, chest, both upper and lower limbs and abdomen. On the next day Bullous lesions were noted on the face and upper limbs, Conjunctivitis, Angioedema, Oral ulcers and blisters on angle of mouth were also observed. These signs and symptoms were started after taking Tab Carbamazepine 100 mg on the 8th day. Based on the patient signs and symptoms the diagnosis was confirmed as Carbamazepine induced Stevens - Johnson syndrome. These Adverse drug reactions may lead to fatal organ failure and skin damage resulting in mortality. Pharmacovigilance which deals with the identification, assessment and prevention of ADRs can help in providing continuous information on medication safety use.
Keywords: Adverse Drug Reaction; Carbamazepine; Stevens - Johnson syndrome.